Surgical complications in 2000 renal transplants - Eufrásio, P (2011)
INTRODUCTION: Renal transplantation is the best treatment for end-stage renal disease. In the last years, we have seen improvements in immunosuppressive treatment, which have allowed patients to experience a better quality of life and graft survival. Nevertheless, surgical complications remain important problems that increase morbidity, mortality, costs, and hospitalization. Our purpose was to evaluate surgical complications among a large series of 2000 renal transplantations. PATIENTS AND METHODS: We retrospectively analyzed all surgical complications among 2000 renal transplants performed between June 1980 and March 2010 in our department. RESULTS: Among 318 (15.9%) surgical complications, 4.8% of patients had urologic problems. Ureteral stenosis and fistula, stent obstruction, and ureteral necrosis occurred in 2.7%, 1.8%, 0.1%, and 0.2% of patients, respectively. Vascular complications reported in 2.7% of patients included arterial or venous thrombosis (1.0% or 0.4%), both arterial and venous thrombosis (0.1%), renal infarction (0.1%), renal artery aneurysm (0.1%) as well as arterial stenosis (0.5%), kinking (0.4%), or dissection (0.1%). Other complications, not specifically related with transplantation surgery, occurred in 4.4% of patients. CONCLUSION: Renal transplantation is a safe surgery by experienced teams. Our rates of surgical complications were within those reported by other series. A meticulous surgical technique is mandatory to prevent them. Prompt diagnosis and management are required to prevent graft damage and patient morbidity.